The Effect of Employee Engagement on Job Satisfaction through Affective Commitment at PT Ultra Medika Surabaya - Dinda Mauliddya (Profesional Muda Cendekia Publishing, 2021)
The purpose of this study was to determine the effect of employee engagement on job satisfaction through affective commitment in employees of PT. Ultra Medika Surabaya. The type of this research is quantitative research with saturated sample technique supported by a sample of 30 employees at PT. Ultra Medika Surabaya. The results of statistical analysis of this study using PLS (Partial Least Square) with PLS 6.0 warp software prove that employee engagement and affective commitment have a significant positive effect on job satisfaction, while employee engagement has a significant positive effect on affective commitment.